Embedding service learning in European higher education - Aramburuzabala Higuera, Pilar; McIlrath, Lorraine; Opazo, Héctor (Routledge, 2019)
"Developed from the successful EU Erasmus+ funded project 'Europe Engage' this book promotes service-learning as a pedagogical approach that develops civic engagement within higher education. By bringing together a range of universities from across Europe and exploring the idea of the civic university through service-learning, this text presents a contemporary view of service-learning and community engagement. It provides conceptual and practical tools for teaching, researching and practicing service-learning and exposes service-learning as a key approach in terms of embedding a culture of political and civic literacy within higher education"--Resumé vydavatel